2009
DOI: 10.11609/jott.o2219.558-61
|View full text |Cite
|
Sign up to set email alerts
|

Status of Bengal Slow Loris Nycticebus bengalensis (Primates: Lorisidae) in Gibbon Wildlife Sanctuary, Assam, India

Abstract: Creative Commons Attribution 3.0 Unported License. JoTT allows unrestricted use of this article in any medium for non-profit purposes, reproduction and distribution by providing adequate credit to the authors and the source of publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…It would appear, however, that the species is generally present in very low densities. That this is not an artefact of the sampling methodology is borne -eastern states of Tripura and Assam, using similar methodology, have resulted in low/nil encounter rates in many sites but high encounter rates in others (Radhakrishna et al 2006;Swapna et al 2008;Das et al 2009). Nekaris and Nijman (2007) reported that encounter rates for Nycticebus bengalensis are 5-15 times lower than for Nycticebus coucang; the results of this survey underline the need to investigate in more detail the factors affecting slow loris abundance in different parts of northeastern India.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear, however, that the species is generally present in very low densities. That this is not an artefact of the sampling methodology is borne -eastern states of Tripura and Assam, using similar methodology, have resulted in low/nil encounter rates in many sites but high encounter rates in others (Radhakrishna et al 2006;Swapna et al 2008;Das et al 2009). Nekaris and Nijman (2007) reported that encounter rates for Nycticebus bengalensis are 5-15 times lower than for Nycticebus coucang; the results of this survey underline the need to investigate in more detail the factors affecting slow loris abundance in different parts of northeastern India.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous research groups have published their survey results, including results from India (Radhakrishna et al 2006, Das et al 2009, Nandini et al 2009), Thailand (Pliosungnoen et al 2010) and Cambodia (Starr et al 2010a,b, Coudrat et al 2011. Most of these surveys cover only single sites or a small number of sites within a restricted part of each respective species' range, thus leaving gaps in our knowledge of their dis tribution.…”
Section: Malaysiamentioning
confidence: 99%
“…In India, the species is confined to the 7 northeastern states (Choudhury 1992, Srivastava 1999, BrandonJones et al 2004, Radhakrishna et al 2006, Swapna et al 2008, Das et al 2009, Nandini et al 2009, Kumar & Devi 2010 and is reported to occur in tropical, subtropical evergreen, semi-evergreen and moist deciduous forests (Choudhury 2001, Swapna et al 2008. Habitat destruction and disturbance due to shifting cultivation, en croachment, selective logging, road kills, bushmeat hunting and forest fire have been reported as major threats to the slow loris population in northeast India (Choudhury 1992, Srivastava 1999, Radhakrishna et al 2006, Kumar & Devi 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, more data are needed to determine the full extent to which the species is affected by such disturbances. Only a few field studies (Mishra et al 2006, Radhakrishna et al 2006, Swapna et al 2008, Biswas et al 2009, Das et al 2009) have been conducted in the last decade in northeast India which confirm the presence of Bengal slow lorises in disturbed (fragmented) and undisturbed habitats and also highlight the conservation issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation